2014
DOI: 10.3762/bjnano.5.238
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer efficacy of a supramolecular complex of a 2-diethylaminoethyl–dextran–MMA graft copolymer and paclitaxel used as an artificial enzyme

Abstract: SummaryThe anticancer efficacy of a supramolecular complex that was used as an artificial enzyme against multi-drug-resistant cancer cells was confirmed. A complex of diethylaminoethyl–dextran–methacrylic acid methylester copolymer (DDMC)/paclitaxel (PTX), obtained with PTX as the guest and DDMC as the host, formed a nanoparticle 50–300 nm in size. This complex is considered to be useful as a drug delivery system (DDS) for anticancer compounds since it formed a stable polymeric micelle in water. The resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This study demonstrated the ability of the targeted liposomal combination to act synergistically and overcome resistance to doxorubicin [8]. A nanosized polymeric complex of paclitaxel showed reversal of drug resistance by mimicking a catalytic reaction, thereby recovering the ability of the paclitaxel to react with its intracellular target at low concentrations [9]. Our group designed and developed cyclodextrin-conjugated lipid nanoparticles, which increased the efficiency of melphalan and were able to recover the cytotoxic activity of the drug in melanoma cells rendered resistant to the free drug [10].…”
Section: Overcoming Drug Resistance At the Cellular Levelmentioning
confidence: 88%
“…This study demonstrated the ability of the targeted liposomal combination to act synergistically and overcome resistance to doxorubicin [8]. A nanosized polymeric complex of paclitaxel showed reversal of drug resistance by mimicking a catalytic reaction, thereby recovering the ability of the paclitaxel to react with its intracellular target at low concentrations [9]. Our group designed and developed cyclodextrin-conjugated lipid nanoparticles, which increased the efficiency of melphalan and were able to recover the cytotoxic activity of the drug in melanoma cells rendered resistant to the free drug [10].…”
Section: Overcoming Drug Resistance At the Cellular Levelmentioning
confidence: 88%
“…The stability of the enzyme-substrate complex is shown as 1/K m , and larger for DDMC/PTX complex than for PTX alone, corresponding to [S] 0 n >>K m . From our previous report [14,[25][26][27], the DDMC/ PTX complex may promote enzymically tubulin polymerization that can be expressed using Michaelis-Menten kinetics added the Hill coefficient [33]. These phenomena also show the supramolecular properties of the DDMC/ PTX complex.…”
Section: Michaelis-menten Kineticsmentioning
confidence: 97%
“…It has been reported that DDMC is superior to other transfection agents with safety efficacy by autoclaved as a non-viral carrier for gene introduction [16][17][18][19][20][21][22][23][24]. On the other hand, the paclitaxel is well known as a strong anti-cancer drug to introduce cancer cells to apoptosis in stabilization of tubulin (i.e., tubulin polymerization) [14,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer efficacy of a supramolecular complex was reported to be used as an artificial enzyme against multi-drug-resistant cancer cells. Tumor actively-targeted theranostic nanoparticles have been developed for therapeutic and diagnostic applications [ 136 , 189 ]. In addition, despite small-molecule drugs, biologics, miRNA, RNA interference (RNAi) and vaccines are under active investigation, the cancer stem cell (CSCs) involved in tumor-induced lymphangiogenesis are now emerging as a plausible target for new drug discovery [ 190 , 191 ].…”
Section: The Role Of Intranodal Lymphatic Sinuses In Cancer Therapmentioning
confidence: 99%